Professional Exodus among Medicos: A Matter of Concern - Surajit Bhattacharya; Kaushik Bhattacharya; Neeta Bhattacharya; Neela Bhattacharya (National Board of Examinations Journal of Medical Sciences)
The phenomenon of sudden professional dropout from the medical field is a multifaceted issue influenced by personal, systemic, and societal factors. Physicians and healthcare workers face unparalleled demands, including prolonged work hours, emotional exhaustion, and significant responsibility, which often contribute to burnout and work-life imbalance. The overwhelming academic pressure, parental and social expectations, limited opportunities at elite medical universities, job market challenges and economic inequality, high living costs and unattainable aspirations, rebellion against the work culture, disillusionment with social mobility and the influence of social media and pop culture lead to professional exodus.